Generational victimhood in post-apartheid South Africa: Perspectives of descendants of victims of apartheid era gross human rights violations - Adonis, Cyril K. (International review of victimology, 2018)
In post-apartheid South Africa, insufficient consideration is given to how historical injustices affect current generations and how they could affect future generations. This has implications for issues such as intergenerational justice and equity. Framed within historical trauma theory and the life-course perspective, this paper explores notions of victimhood in post-apartheid Africa. It draws on qualitative interviews conducted with 20 children and grandchildren (10 females and 10 males) of victims of apartheid-era gross human rights violations. The interview data, which were interpretively analysed, yielded a number of salient themes. Participants' sense of victimhood is anchored in their continuing socio-economic marginalisation deriving from the structural legacy of apartheid, as well as the pervasive racism that continues to bedevil South Africa well into the post-apartheid era. This is compounded by the perceived lack of accountability for historical injustices and the responsibilities that they perceive the government to have towards them. Given this, the paper argues for a reconceptualisation of the notion of victimhood and giving greater consideration to the impact that the structural legacy of apartheid has on the contemporary existential realities of Black South Africans.